1960
DOI: 10.1104/pp.35.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2,4-Dichlorophenoxyacetic Acid on Pathways of Glucose Utilization in Bean Stem Tissues

Abstract: is essentially the same as described in a previous paper (2). The air flow rate through each train can be checked and adjusted independently by means of a bypass manifold attached to a flowmeter. Respiratory CO2 from each flask was continuously swept out by a stream of CO.,-free air and absorbed in individual CO, traps. Flasks were shaken continuously in the light for six hours at 260 C. The respiratory CO., samples obtained during an experiment were precipitated as BaCO1 and the radioactivity determined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, the acetyl-CoA produced by the stimulation of the fatty acids beta oxidation might have entered the Krebs cycle instead of the glyoxylate cycle in the pea stems. Previous studies showed that 2,4-D increased the respiration rate in the stems of susceptible plants (Fang et al 1960(Fang et al , 1961Key et al 1960). Other studies also showed that the stems of 2,4-D-treated plants, in which an abnormal overgrowth took place, contained more proteins and nucleic acids, and less nuclease activity, than the stems of untreated plants (Key and Hanson 1961;Chrispeels and Hanson 1962;Shannon et al 1964;Cárdenas et al 1968).…”
Section: Resultsmentioning
confidence: 96%
“…Thus, the acetyl-CoA produced by the stimulation of the fatty acids beta oxidation might have entered the Krebs cycle instead of the glyoxylate cycle in the pea stems. Previous studies showed that 2,4-D increased the respiration rate in the stems of susceptible plants (Fang et al 1960(Fang et al , 1961Key et al 1960). Other studies also showed that the stems of 2,4-D-treated plants, in which an abnormal overgrowth took place, contained more proteins and nucleic acids, and less nuclease activity, than the stems of untreated plants (Key and Hanson 1961;Chrispeels and Hanson 1962;Shannon et al 1964;Cárdenas et al 1968).…”
Section: Resultsmentioning
confidence: 96%
“…Whlen bean stem tissue was usedl in a ra(lio-respirometric experiment, 2,4-D causedl a dlecrease in the anmounlt of glucose catabolized via the pentose phosphate pathway (1). Since acetate occupies a key positioln in the metabolic patbiways of amino acids, carbohydlrates, and fatty acids, the effect of In the experiments with steml tissue, the total amount of 2,4-D was applied to each plant along the midrib of one primary leaf, wNhile in the experinments with leaf tissue, the aimiount of 2,4-D was equally divide(l and applied to both primary leaves.…”
mentioning
confidence: 99%
“…Altlhough the basic mechanism of action of plant hormones is not known, there is some evidence that indole-acetic acid (IAA) exerts an effect on pathways as well as rates of respiratory metabolism (7,9,10,15). The influence of plant hormones on metabolism may be critically important to understanding obligate parasitism.…”
Section: Introductionmentioning
confidence: 99%